2019
DOI: 10.15547/tjs.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell reaction to acupuncture on tongue

Abstract: PURPOSE: The aim is to find out the mast cells (MCs) reaction in tongue after experimental acupuncture. METHODS: For experiments were carried 10 adults rats (28 months age). The needles used for the acupuncture is 0.22x13mm, and were placed for 10 minutes into standard acupuncture point Ex-HN-10 (Juquan) corresponding to that of humans. This point is located on the upper surface in the sagittal plane of the tongue and is close to the center of the tongue body. As normal consequence of every acupuncture is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…LM and EM confirmed that MCs in the tongue and liver were connective tissue (CT) MCs, which is consistent with published reports [12,15,21,[63][64][65][66][67][68][69][70][71]. LM showed that MCs were distributed across the entire dorsal surface in all TBstained tongue tissue samples (Fig.…”
Section: Characterization Of Mcs In Tonguesupporting
confidence: 90%
“…LM and EM confirmed that MCs in the tongue and liver were connective tissue (CT) MCs, which is consistent with published reports [12,15,21,[63][64][65][66][67][68][69][70][71]. LM showed that MCs were distributed across the entire dorsal surface in all TBstained tongue tissue samples (Fig.…”
Section: Characterization Of Mcs In Tonguesupporting
confidence: 90%
“…MCs were shown to be intensely present near blood vessels and between glands in microscopic papillae and in compact tissue beneath the epithelium of the tongue surface (Karaca & Yörük, 2004). Furthermore, it has been stated that MCs were scattered throughout the lamina propria and in the deep muscular layer in the rat tongue (Pirovski et al., 2018). In this study, MCs were found more densely around glands, between muscle bundles, especially deep muscular layer and particularly in the dorsal part of the tongue, in the subepithelial region.…”
Section: Discussionmentioning
confidence: 99%
“…132 Such observations are generally applicable to major markets such as China. 133 In this regard, the EU is taking the lead with a detailed set of regulations concerning the classification of ESG disclosures and disclosure obligations introduced under the EU Taxonomy Regulation and the EU Regulation on Sustainability-related Disclosures. 134 In tightening the standard of sustainability information disclosure, legislators could borrow salient ideas from established standards of professional organisations.…”
Section: Exit Stagementioning
confidence: 99%